The influence of the solution of their amount on the process of water splitting by the electrolysis method - Kuanyshbekova, A.B.; Serikov, T.M.; Zhanbirbayeva, P.A.; Sadykova, A.E.; Beisembaeva, G.T.; Baltabekov, A.S. (KU Publ., 2022)
The article presents the results of an experimental study of the effect of the solution and their concentration on the process of splitting water by electrolysis under the action of a direct electric current using a Hoffman device. As solutions, we used sodium hydroxide, sodium phosphoric acid, sodium carbonate, sodium sulfate, sodium metaborate, sodium phosphoric acid 2 — substituted and potassium hydroxide. The number of salts in the solution varied from 0.2 mol to 0.8 mol. The study showed that the splitting water at constant current and voltage is influenced by both the nature of salts and their quantity. So, it was found that with the same amount of substances in the solution, the process of splitting water occurs faster in a solution containing potassium hydroxide. When using an aqueous KOH solution in an amount of 0.2 mol, the volume of hydrogen released was 15 ml, and at 0.8 mol, 19.5 ml. Using an aqueous solution of sodium metaborate with a similar concentration, the volume of hydrogen released was 2 ml and 4.5 ml, respectively. The obtained results allow to choose the solution and its amount during the process of photocatalytic splitting of water.
Суды электролиз әдісі арқылы ыдырату кезінде ерітіндінің және оның мөлшерінің әсері
Влияние раствора и его количества на процесс расщепления воды методом электролиза
Keywords: water splitting; Hofmann apparatus; electrolysis; hydrogen; salt; solution; reactions; electrochemical process